Propagación in vitro y aclimatización de Euchile mariae (Ames) Withner (Orchidaceae) - Suárez-Quijada, Iris (Universidad de Costa Rica, 2015)
Orchid micropropagation of species Euchile mariae was achieved from the in vitro culture of protocorms sections, obtained from the germination of seeds. The top and bottom protocorms sections, used as explants, were cultivated in modified MS culture medium, added with different concentrations of α-naph- thaleneacetic acid (NAA) and 6-benzylaminopurine (BA). The morphogenetic response obtained of both types of explants, was the formation of protocorm like bodies (PLB’s), that gave place to the formation of new plantlets. Of two tested explants the biggest formation of PLB’s was obtained from the bottom proto- corms sections. The acclimatization of the plantlets was successful, with a 100% percent survival. Plant cell tissue culture represents a useful alternative for the study, conservation and massive propagation of this and other endangered species.